Legal Protection of BOT Agreement in Korea Town Project: Supreme Court Decision Number 600K/Pdt/2018 - Andreas Edy Saputra Nainggolan; Diana Napitupulu; Ani Wijayati (Jurnal Hukum Magnum Opus, 2026)
This study analyzes legal protection in Build, Operate, and Transfer (BOT) agreements through examination of Supreme Court Decision No. 600K/Pdt/2018 concerning The High End City Korea Town (THECKT) project. of Indonesia Number 600K/Pdt/2018. The purpose of this research is to analyze the application of the principles of justice and balance in the legal relationship between the landowner and the investor, as well as to assess the extent of legal protection granted to the parties in the event of unilateral termination of the BOT agreement. The research employs a normative juridical method with statutory, case, and comparative approaches. The data consist of primary and secondary legal materials, along with relevant non-legal materials. The analysis is conducted qualitatively using deductive reasoning. The findings reveal that unilateral termination without clear legal grounds violates the principle of legal protection and may cause economic losses to investors. The Supreme Court’s decision affirms that BOT agreements must be interpreted through the pri. Unilateral termination of the agreement without clear legal grounds constitutes a violation of the principle of legal protection and may cause economic losses to the investor. Therefore, the application of the principle of justice as proposed by John Rawls’ theory of justice and the principle of balance in contract law serves as an essential foundation to create a fair and proportional legal relationship in the implementation of BOT agreements in Indonesia.